Optimization of incubation time of protein Tc85 in the construction of biosensor: Is the EIS a good tool? - Pupim Ferreira, Antonio Ap. [UNESP]; Alves, Maria Julia M.; Barrozo, Sidineia [UNESP]; Yamanaka, Hideko [UNESP]; Benedetti, Assis Vicente [UNESP] (Elsevier B.V. Sa, 2010)
Electrochemical impedance spectroscopy (EIS) in pH 6.9 phosphate buffer solution was used to investigate each step of the procedure employed to modify a screen-printed electrode (SPE). The SPE was modified with self-assembled monolayers (SAMs) of cystamine (CYS, deposited from 20 mM solution), followed by glutaraldehyde (GA, 0.3 M solution). The Trypanosoma cruzi antigen was immobilized using different deposition times. The influence of incubation time (2-18 h) of protein was also investigated. The topography of modified electrode with this protein was investigated by atomic force microscopy (AFM). Interpretation of impedance data was based on physical and chemical adsorption, and degradation of the layer at high and meddle frequencies, and charge transfer reaction involving mainly the reduction of oxygen at low frequencies. EIS studies on modified electrodes with Tc85 protein immobilized for different incubation times indicated that the optimum incubation time was 6-8 h. It was demonstrated that EIS is a good technique to evaluate the different steps and the integrity of the surface modifications, and to optimize the incubation time of protein in the development of biosensors. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Electrochemical impedance; Electrode modification; Protein incubation time; SAM; T. cruzi